Home-based business for dummies - Edwards, Paul 1940-; Edwards, Sarah (Sarah A.).; Economy, Peter (Hoboken, N.J. Wiley, 2010)
This guide to running a successful business from the home includes information on a wide range of financial planning, tax, marketing, and technological issues.
Keywords: Home-based businesses; New business enterprises